2017
DOI: 10.1101/211631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between sexual habits, menstrual hygiene practices, demographics and the vaginal microbiome as revealed by Bayesian network analysis

Abstract: 20The vaginal microbiome plays an influential role in several disease states in reproductive age 21 women, including bacterial vaginosis (BV). While demographic characteristics are associated 22 with differences in vaginal microbiome community structure, little is known about the influence 23 of sexual and hygiene habits. Furthermore, associations between the vaginal microbiome and risk 24 symptoms of bacterial vaginosis have not been fully elucidated. Using Bayesian network (BN) 25 analysis of 16S rRNA gene s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…hormonal changes associated with menses) and exogenous factors (e.g. contraception, sexual intercourse, hygiene practices) [24][25][26] . It is therefore striking that VMB composition at baseline associates with CIN2 regression or nonregression 12 and 24 months later, suggesting long-term interaction between vaginal bacterial composition and CIN2 natural history, however further studies on more densely sampled women would be required to elucidate this further.…”
Section: Discussionmentioning
confidence: 99%
“…hormonal changes associated with menses) and exogenous factors (e.g. contraception, sexual intercourse, hygiene practices) [24][25][26] . It is therefore striking that VMB composition at baseline associates with CIN2 regression or nonregression 12 and 24 months later, suggesting long-term interaction between vaginal bacterial composition and CIN2 natural history, however further studies on more densely sampled women would be required to elucidate this further.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between the microbiota plus background variables and clinical outcomes in different stages of a woman’s life are complex, and which intrinsic or external factors drive the community composition it is not fully understood 61 , 62 . Behavioral factors, such as sexual behavior and methods of birth control, may contribute to lactobacilli reduction and leading to an intermediate microbiota or even a vaginal infection 54 , 63 65 . The present study showed the results of the vaginal microbiota colonization in Ecuadorian women from Pichincha province (considered as another ethnicity factor), after controlling the confounding factors, such as sociodemographic, behavioral or environmental variables.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are associated with shifts in vaginal bacterial content, with menses representing the phase in which the microbiome is more diverse, while the oestradiol and progesterone peaks are more bacterially stable times . Some external factors can also modulate the vaginal microbiota, such as hygiene habits, sexual exposure, change of sexual partners, and use and type contraceptives . The factors influencing the structure and composition of the cervicovaginal microbiota were recently reviewed by Kroon and colleagues (Figure ) …”
Section: Female Reproductive Tract Microbiotamentioning
confidence: 99%